Numerical simulation of the water surface movement with macroscopic particles on movable beds for inhomogeneous relief. Issue 1 (2nd January 2022) - Issakhov, Alibek; Borsikbayeva, Aliya
ABSTRACT: In the proposed work, a numerical model of the water flow during dam breakthrough using the volume of fluid (VOF) method is constructed. The mathematical model consists of a system of Navier–Stokes equations, and also includes equations for the phase and motion of particles. For the simulation, the SST k − ω turbulent model was used. To solve the system of equations, the PISO algorithm was used. The reliability and accuracy of the developed 3D model were validated using a laboratory experiment on the problem of dam-break. The obtained results of the problem were compared with the calculations of other authors and with experimental data. The comparisons show good consistency and generally yielded positive results. Also in this work, the natural mudflow was maximally close to reality: with the presence of both deposits of mud mass and imitating particles and dam fragments of particles in an obstacle of a trapezoidal shape.